2019
DOI: 10.1002/mus.26719
|View full text |Cite
|
Sign up to set email alerts
|

Severity and depression can impact quality of life in patients with myasthenia gravis

Abstract: Background: The revised 15-item Myasthenia Gravis (MG) Quality of Life Questionnaire (MGQoL15R) is a validated scale of quality of life in patients with MG. We aimed to study the factors causing the variability within the Arabic version of the MGQoL15R (MGQoL15R-A). Method: A standardized questionnaire was completed by 118 patients. Correlations and hierarchical regression analyses were used to assess the contribution of sociodemographic variables, clinical factors, Patient Health Questionnaire-9 (PHQ9-A), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…In terms of drug use characteristics, number of relapses, severe MAUD, and comorbidity with OUD negatively predicted at least one domain of QOL. First, more relapses predicted poorer PHYSQOL and SOCIALQOL, which was consistent with the findings of some recurrent diseases such as acne (53), depression (54) and SUDs (55). Our findings suggested that relapse was an important risk factor for QOL of SUDs patients, especially in their physical and social domains.…”
Section: Discussionsupporting
confidence: 85%
“…In terms of drug use characteristics, number of relapses, severe MAUD, and comorbidity with OUD negatively predicted at least one domain of QOL. First, more relapses predicted poorer PHYSQOL and SOCIALQOL, which was consistent with the findings of some recurrent diseases such as acne (53), depression (54) and SUDs (55). Our findings suggested that relapse was an important risk factor for QOL of SUDs patients, especially in their physical and social domains.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, frequent relapses with hospitalization or ER visit profoundly affect the quality of life of the patients with MG. Relapse of MG, along with high disease severity and unresponsiveness to treatment, is associated with depression ( 18 , 19 ), and the association between depression and worse quality of life has been consistently suggested in previous reports ( 20 , 21 ). Other study showed that recent relapse of MG itself is associated with low quality of life ( 22 ). In addition, frequent hospitalization also imposes a considerable financial burden to the patients ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed 635 single LPE sessions in 276 individual patients, which represent the largest retrospective cohort on LPE therapy to date. Previously, the investigators noticed encouraging therapeutic effects of LPE on several cases of acute systemic lupus erythematosus, rheumatoid arthritis, and acute renal allograft rejection ( 9 , 10 , 17 ). Recently, Luo et al.…”
Section: Discussionmentioning
confidence: 99%